Acetabular Coverage May Affect Radiographic and Clinical Outcomes of Osteochondral Allograft Transplantation of Focal Femoral Head Lesions: A Case Series From a Single Institution. (12th October 2021) - Mundluru, Surya N.; Podeszwa, David; Peck, Jeffrey; Sucato, Dan; Johnston, Charlie; Kim, Harry; Wilson, Philip; Ellis, Henry
Abstract : Osteochondral lesions of the femoral head in young people are rare and present unique management challenges. Optimal treatment for these lesions is unclear. From 2009 to 2016, clinical and radiographic outcomes were prospectively collected within a series of symptomatic focal osteochondral lesions of the femoral head with a minimum follow-up of 2 years. A surgical hip dislocation followed by implantation of a size-matched fresh osteochondral femoral head allograft was performed. Nine hips in eight patients (6 female patients) underwent surgery at an average of 17 years (11 to 21 years). Individual allograft sizes ranged from 10 to 35 mm in diameter; with 2 of 9 hips receiving two allografts in a stacked or mosaicplasty technique at the time of treatment. The average graft implantation was 3536.5 mm 2 . Modified Harris hip scores improved by 13.4 ( P = 0.018) from preoperative to final follow-up for all patients. Significant improvements in internal rotation (12° versus 23°, P = 0.011), external rotation (32° versus 50°, P = 0.041), and abduction (28° versus 40°, P = 0.042) were also achieved. Three patients (four hips) demonstrated poor radiographic healing (<50% incorporation at 2 years), which correlated with worse clinical outcomes and was associated with a lower preoperative lateral center edge angle (21.5° versus 30.4°, P = 0.049). Fresh osteochondral allograft treatment is a good option for focal osteochondral lesions of the femoral head with improved outcomes and motion; however, higher failure rates may be seen in those with a lower center edge angle.